Peranan Badan Musyawarah Nagari dalam Penyaluran Aspirasi Masyarakat - Silvia Evandri; Henni Muchtar; Fatmariza Fatmariza; Yusnanik Bakhtiar (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study aims to determine the role of the Bamus in Nagari Pasir Talang as a channel for community aspirations. This type of research is qualitative with phenomenological methods. Presentation of data is described in the form of descriptive descriptions. Data collection was carried out by means of interviews, observation, and documentation studies. Research informants consisted of the Head of the Bamus and its members, village assistants, Wali Nagari office staff, community leaders and the Nagari Pasir Talang community. Data analysis techniques were carried out with the stages of data collection, data reduction, data presentation, and data verification. The results showed that the Bamus in Nagari Pasir Talang had not carried out their role optimally. This is due to the obstacles faced by the Bamus in carrying out its role. One of the main factors constraining the sub-optimal role of the Bamus in Nagari Pasir Talang is that the Bamus has not carried out its main duties and functions within the community. This has an impact on development in Nagari Pasir Talang which tends to be slow. The existence of the Bamus in Nagari Pasir Talang has not fully played an optimal role and has not had a significant developmental impact on the progress of the Nagari.